Odpowiedzi

2010-02-17T14:55:54+01:00
A) 4x-7 < 2x+3
4x-2x<3+7
2x<10
x<5

b) -x+4>-3*(x-1)
-x+4>-3x+1
-x+3x>1-4
2x>-3
x<-1,5

c) 5* (2x-3)-6x>(równy)3*(4x-3)
10x-15-6x≥12x-9
4x-15≥12x-9
4x-12x≥-9+15
-8x≥7
x≤-7/8

d) -0,2*(5x-3) <(równy)x-0,1
-x+0,6≤ x-0,1
-x-x≤-0,1-0,6
-2x≤-0,7
x≥0,35
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-17T14:58:25+01:00
A) 4x-7 < 2x+3
2x<10
x<5
b) -x+4>-3*(x-1)
-x+4>-3x+3
-4x>7
x<-7/4
x<-1¾

c) 5* (2x-3)-6x≥3*(4x-3)
10x-15-6x≥ 12x-9
4x-15≥12x-9
-8x≥6
x≤6/8
x≤¾

d) -0,2*(5x-3) ≤x-0,1
-x+0,6≤x-0,1
-2x≤0,7
x≥0,35